Effects of crown-to-implant ratio on marginal bone level and bone density in non-splinted single implants: a cross-sectional study - Ziyuan Chen; Weiting Li; Peng Li (BMC, 2023)
Abstract Background Few studies have evaluated the effects of the crown-to-implant (C/I) ratio on the marginal bone level (MBL) and bone density in non-splinted single implants. The aim of this study was to assess the effect of C/I ratio on MBL and density of peri-implant bone in non-splinted posterior implants. Methods The C/I ratio, MBL, and grayscale values (GSVs) for bone density were measured from X-rays. Four areas of interest (two at the apical area and two at the middle of the peri-implant area) and two control areas were selected for evaluation. Follow-up radiographs were calibrated according to the control areas. Results In all, 117 non-splinted posterior implants in 73 patients followed up for a mean duration of 36.23 ± 10.40 (range 24-72) months were considered. The mean anatomical C/I ratio was 1.78 ± 0.43 (range 0.93 to 3.06). The mean change in MBL was 0.28 ± 0.97 mm. There were no significant associations between the C/I ratio and MBL changes (r = -0.028, p = 0.766). Pearson correlation showed a significant correlation between changes in GSV and the C/I ratio in the middle peri-implant area (r = 0.301, p = 0.001) and apical area (r = 0.247, p = 0.009). Conclusions A higher C/I ratio of single non-splinted posterior implants is associated with increased peri-implant bone density, but not correlated with changes in MBL.